# How do you solve #x-(3/x) = -2#?

You can start by lowest common denominator

Now, just find the roots:

(I'll use Bhaskara)

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation x - (3/x) = -2, we can follow these steps:

- Multiply both sides of the equation by x to eliminate the fraction: x(x) - (3/x)(x) = -2(x).
- Simplify the equation: x^2 - 3 = -2x.
- Rearrange the equation by moving all terms to one side: x^2 + 2x - 3 = 0.
- Factor the quadratic equation: (x + 3)(x - 1) = 0.
- Set each factor equal to zero and solve for x: x + 3 = 0 or x - 1 = 0.
- Solve for x in each equation: x = -3 or x = 1.

Therefore, the solutions to the equation x - (3/x) = -2 are x = -3 and x = 1.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7